Analisis Internal Control Sistem Keuangan Desa (Siskeudes) Untuk Meningkatkan Kualitas Laporan Keuangan Pemerintah Desa - Alina Widyasari,; Esta Ifani Chairun Nisa,; Saiful Anwar, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
Research on the analysis of internal control and the village financial system (siskuedes) on the quality of the financial statements of the village government aims to implement an accounting system that can play a role in producing a quality financial report. Internal control is needed so that it is easy to find or analyze existing problems or problems that might arise in the process of achieving goals so that we can know clearly the achievement of objectives. Good internal control can also provide adequate confidence about financial statement activities. The object in this study is the quality of financial statement in the village government. The method used is a qualitative method. Qualitative method is a descriptive research method, used analysis, refers to data, utilizes existing theories as supporting material, and produces a theory. The results of this study indicate ability of internal control siskeudes is crucial in reporting and preparing village government finances. The performance competency carried out by internal control is very significant where the competency carried out by the organizational with this performance can moderate the relationship with the village financial system to the quality of financial statements.